Modern presentetion technologies in distant learning systems - Mateljan, Vladimir (Array, 2009)
All modern distant learning system are designed as three-tiers systems, consisting of data tier, application tier and presentation tier. Such arhitecture has been dominant from the very beginning of development of distance learning systems, because of its characteristics: independancy of tiers, extensibility of the whole system and system scalability, that allowed support for increasing number of users. Users of distance learning systems mostly see and use presentation tier, so it is not surprising that presentation tier was the one part of distance learning systems that has passed through biggest evolutionary changes. The increase of computer networks' throughput, the increase of strength and speed of graphical processing units in home and office users' computers, and the advent of modern operation systems have allowed intensive advance of multimedia in all digital contents, including learning contents. Modern learning contents are inconcievable without multimedia elements, first of all video, which is becoming indispensable media for learning. Because of aforementioned reasons, this paper will outline historical development of presentation technologies in distant learning systems. It will present their current status and, based on available trends, will try to give a projection in which direction are presentation technologies headed and how could they look in the future. Special review will be given on new presentation technologies Silverlight and XAML, and on incoming average user's standard, operation system Windows 7.